Ambiência [trans] formativa na educação superior: processos de resiliência no início da carreira docente - Trevisan, Neiva Viera (2014)
This present thesis has as central theme the initial years of teaching in Higher Education within the framework of teacher education, in other words, the protagonists of investigation are novice teachers at a teacher education program graduate entering teaching. The general objective was to investigate how if constitutes the teaching in beginning of career in higher education, considering the ambience, the formative processes and teaching resilience through narrative reconstruction of the initial trajectory of teacher educators at a public university . The subjects, novice teachers working at the Centro de Educação, Universidade Federal de Santa Maria (CE/UFSM), accepted to share their experience, by Statement of Informed Consent - SIC. It is a qualitative search of autobiographical narrative approach, the methodological process involved: [1] exploratory questionnaire to identify the subjects that meet the criteria of time teachers in public higher education and [2] narrative interviews recorded and transcribed. The analysis and interpretation of data were developed by way of Textual Discourse Analysis (TDA), the optical of Roque Moraes (2003). The definition of theoretical-conceptual was constructed as from the following concepts: teaching resilience (GROTBERG, 2005; YUNES; TAVARES , 2001; SOUSA, 2009), formation (IMBERNÓN, 2009a, 2009 b, 2010; NÓVOA, 1998; 2007; HUBERMAN, 1995; ABRAHAM, 2000; ESTEVE, 1992; ARROYO , 2009), narratives (JOSSO, 2010); beginning of teaching career (RUÍZ, 2008; MARCELO GARCIA , 2009), higher education (ISAÍA; BOLZAN, 2011) and ambience [trans] formative (MACIEL, 1995; 2000; 2006; 2009; 2010; MACIEL; TREVISAN, 2013). We hope to have contributed to the education and formation of teachers for the higher education, with a theoretical contribution that brings the discussion the topic of beginning teaching career in higher education, considering the ambience [trans] formative, the formative processes and the teaching resilience, pointing to the needs, on the one hand, sensitive listening to novice teachers and their needs and, on the other hand, the institutions of higher education take into account in their admission policies and permanence of teachers not only the reception in beginning career, as also the formation and the teachers professional development.